PENINGKATAN KREATIVITAS ANAK USIA DINI MELALUI KEGIATAN KOLASE MENGGUNAKAN BAHAN ALAM DI PAUD KASIH BUNDA KECAMATAN LUAS - Ermani Ermani; Elise Muryanti (STKIP Subang, 2026)
This research is motivated by the low creativity of early childhood children in art learning activities at Kasih Bunda Early Childhood Education School, Luas District, Kaur Regency. This condition is seen from the tendency of children to imitate examples given by teachers, less able to develop their own ideas, and low variation in producing works. This study aims to improve the creativity of early childhood children through collage activities using natural materials. The study used the Classroom Action Research (CAR) method model Kemmis and McTaggart which consists of the planning, action, observation, and reflection stages carried out in two cycles. The research subjects were 10 children in group B aged 5–6 years. Data collection techniques were carried out through observation, documentation, and performance assessment. Data were analyzed using qualitative and quantitative descriptive techniques in the form of percentages. The results of the study showed that collage activities using natural materials were able to significantly increase children's creativity. In the pre-cycle stage, the level of completeness of children's creativity reached 40% with an average score of 57.5. After the action in Cycle I, the completeness increased to 60% with an average score of 67.5. In Cycle II, completion increased to 90% with an average score of 85. Improvements were seen in children's ability to generate ideas, use various materials, create unique works, work more neatly, and demonstrate perseverance in completing tasks. Thus, collage activities using natural materials have proven effective in enhancing early childhood creativity and can be used as an interesting, fun, and meaningful learning alternative in PAUD.